Use of acetylsalicylic acid and agronomic performance of potatoes in Lima region - Sergio Contreras-Liza; Luis Vargas-Luna (CABI Agriculture and Bioscience)
Abstract Background Salicylic acid participates in the regulation of the plant's response to a series of environmental stresses such as extreme temperatures, salinity, and oxidative condition of potato growth, so it is necessary to determine a safe application dosage for potato in field conditions. Methods The purpose of the research was to evaluate the effect of increasing doses of acetylsalicylic acid on the agronomic traits of two potato cultivars in Lima, Peru. In a field experiment, an RCBD with 3 replications was used under a split-plot arrangement in which five doses (0.0, 0.2, 0.4, 0.6, and 0.8 mM) of acetylsalicylic acid plus control with Biol (biostimulant) were assigned to plots, and two potato cultivars ('Perricholi' and 'Unica') were assigned to subplots. The average temperatures were between 15 and 21º C, the air relative humidity was between 61 and 73% and the soil was loam textural class, free of salts. Results No statistical differences were found for the number and weight of tubers and biomass due to the effect of the application of the treatments. The effects of doses of acetylsalicylic acid showed statistical differences for sprouting, vegetative vigor, and percentage of flowering; likewise, significant interactions (p < 0.05) were shown between potato cultivars and dose of acetylsalicylic acid for the number of stems per plant and percentage of flowering, which indicated a specific effect for the dose of acetylsalicylic acid in each potato cultivar. Statistical differences (p < 0.05) were found between the two potato cultivars for most of the characters studied. Conclusion No dose of the product significantly affected the potato yield in two potato cultivars however, the effect of the dosage of acetylsalicylic acid improved the performance of the crop in terms of sprouting in the field, vegetative vigor, a greater number of stems per plant as well as stimulation of flowering, with respect to control.